(untitled) (Politeja, 2019)
This paper discusses issues with law enforcement and compliance in the area of public international law. It presents the conditions affecting the quality of the application of legal norms of public international law. Analysis of the problem is multifactorial. While presenting the law enforcement process, attention is drawn to the question of the standards of execution of international legal norms that run contrary to national law. This phenomenon has been identified as and called by the authors “discovering law (legal norms) through sanctions”. The main issue concerns theoretical and legal philosophical issues: the legal responsibility of states, coercive measures against states, sanctions and countermeasures in public international law and in international relations. The authors critinstitutionalization and heterogenity of public international lawicize the contemporary model of the legal responsibility of states, pointing to a feedback loop between the concept of sanctions and the principle of the sovereigntyof a state. Homogenization and globalization processes overlap only slightly in public international law. Also, institutionalization and constitutionalization have slowed. We argue that the PIL system is threatened by the effects of sui generis rejection of legal norms by a state in relation to certain countries while claiming that these legal norms apply to other countries. The system is also under threat by the effects of strong nationalist tendencies among PMP actors, as well as the international community itself. The conclusion and recommendation of the authors suggest that the lack of analysis of socio-legal publicinternational law is undesirable and harmful to that area of law. We claim that itnegatively affects macro-social efficiency and, above all, the supranational and interstate (intergovernmental) level of effectiveness. It impairs the process of institutionalization of public international law and hinders the process of socialization, sensu largissimo.